2023
DOI: 10.1108/bpmj-01-2023-0024
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation and export performance: a process mechanism of firm digital capabilities

Abstract: PurposeThis study aims to investigate the logic between digital transformation and export performance by analysing a large sample of Vietnamese exporters. The theoretical model is further extended by investigating the driving role of digital transformational leadership and mediating effects of firm digital capabilities and employee exploration and exploitation innovation.Design/methodology/approachThe study sample comprised 364 middle managers at 107 export firms in Ho Chi Minh City, Vietnam. The data are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 152 publications
1
4
0
Order By: Relevance
“…First, it is found that transformational leadership and digital transformation are positively related. When the literature is reviewed, it is seen that many studies emphasize the importance of leadership for digital transformation, and there is also research examining the relationship between transformational leadership and digital transformation [13,99,100]. Our finding is consistent with these results.…”
Section: Discussionsupporting
confidence: 89%
“…First, it is found that transformational leadership and digital transformation are positively related. When the literature is reviewed, it is seen that many studies emphasize the importance of leadership for digital transformation, and there is also research examining the relationship between transformational leadership and digital transformation [13,99,100]. Our finding is consistent with these results.…”
Section: Discussionsupporting
confidence: 89%
“…The term readiness encompasses awareness, ability, and willingness to digitalize [22], [23]. Although the premise of the DRT seems to provide justifications to assert that digital readiness is likely to influence BPD and possibly performance, there seems to be insufficient empirical evidence linking the two phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019). Organisational culture is crucial to enable quick adjustments to changes to different skills and technologies in the demand for successful digital transformation (Luu, 2023). Moreover, organisations with better technological capabilities and good organisational culture are less dependent on external pressures for digital transformation (Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Digital capabilities are an important dynamic capability that can help organisations to identify opportunities to respond to challenges quickly and enhance organisational resilience (Chen et al, 2023), working as a driving force and mechanism for digital transformation (Luu, 2023). These capabilities impel organisations to implement changes to improve or maintain their competitive advantage (Vial, 2019;Zhu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%